Analisis Perbandingan Perencanaan Dan Pelaksanaan Pada Time Schedule Pembangunan Struktur Ruko 3 Lantai Dengan Metode CPM dan PERT (Studi Kasus: Regency Piayu) - Victory, Jeffrey; Indrastuti, Indrastuti (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2025)
Time management is critical to a project's success because it makes it easier to create controls that guarantee the project is carried out with few deviations and produces satisfactory outcomes with the resources already in place. The PERT and CPM methodologies are designed to describe and establish relationships between various activities and interpret the varying times required for each activity in a comprehensive project plan. The author's investigation focused on the construction of a 3-story shophouse. Based on this investigation, it was found that the planning time to complete the structural work was 50 weeks, while the implementation (realization) was 54 weeks to complete the structural work. In addition, to prevent delays in construction projects, it is necessary to prioritize several tasks designated as critical paths. Using the critical route method, it was discovered that the installation of the first and second floor staircase work, which took longer than expected (15 weeks), was the primary reason for delays compared to the free float given, namely 8 weeks. The results of this study offer valuable suggestions for possible future investigations